Factors Affecting the Performance of MSMEs in Demak Regency with HR Competence as a Moderating Variable - Retno Tri Handayani; Khoirul Fuad; Diah Ayu Susanti (Jurnal Riset Akuntansi Terpadu, 2023)
MSMEs have a very important role to support the national economy. It is very important to try to maximize the performance of SMEs. The better performance of MSMEs is expected to be able to survive in the midst of less strategic conditions. This study used a quantitative method by distributing questionnaires to SMEs in Demak City, Central Java. The results of this study indicate that business strategy can influence the performance of MSMEs in a positive direction. Likewise with the influence of HR competence on MSME performance. However, HR competence is not able to moderate the effect of business strategy on MSME performance.